Expanding the spectrum of shallow-marine, mixed carbonate–siliciclastic systems: processes, facies distribution and depositional controls of a siliciclastic-dominated example - Schwarz, Ernesto (2018)
Most of the present knowledge of shallow-marine, mixed carbonate–siliciclastic systems relies on examples from the carbonate-dominated end of the carbonate–siliciclastic spectrum. This contribution provides a detailed reconstruction of a siliciclastic-dominated mixed system (Pilmatu e Member of the Agrio Formation, Neuqu en Basin, Argentina) that explores the variability of depositional models and resulting stratigraphic units within these systems. The Pilmatu e Member regressive system comprises a storm-dominated, shoreface to basinal setting with three subparallel zones: a distal mixed zone, a middle siliciclastic zone and a proximal mixed zone. In the latter, a significant proportion of ooids and bioclasts were mixed with terrigenous sediment, supplied mostly via along-shore currents. Storm-generated flows were the primary processes exporting fine sand and mud to the middle zone, but were ineffective to remove coarser sediment. The distal zone received low volumes of siliciclastic mud, which mixed with planktonic-derived carbonate material. Successive events of shoreline progradation and retrogradation of the Pilmatu e system generated up to 17 parasequences, which are bounded by shell beds associated with transgressive surfaces. The facies distribution and resulting genetic units of this siliciclastic-dominated mixed system are markedly different to the ones observed in present and ancient carbonate-dominated mixed systems, but they show strong similarities with the products of storm-dominated, pure siliciclastic shoreface–shelf systems. Basin-scale depositional controls, such as arid climatic conditions and shallow epeiric seas might aid in the development of mixed systems across the full spectrum (i.e. from carbonate-dominated to siliciclastic-dominated end members), but the interplay of processes supplying sand to the system, as well as processes transporting sediment across the marine environment, are key controls in shaping the tridimensional facies distribution and the genetic units of siliciclastic-dominated mixed systems. Thus, the identification of different combinations of basin-scale factors and depositional processes is key for a better prediction of conventional and unconventional reservoirs within mixed, carbonate–siliciclastic successions worldwide.